2020
DOI: 10.1021/acs.est.9b06825
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Bromide Removal from Shale Gas Produced Water by Unactivated Peroxymonosulfate for Controlling Disinfection Byproduct Formation in Impacted Water Supplies

Abstract: Shale gas extraction processes generate a large amount of hypersaline wastewater, whose spills or discharges may significantly increase the bromide levels in downstream water supplies and result in the formation of brominated disinfection byproducts (DBPs) upon chlorination. Although a few studies have investigated selective bromide removal from produced water, the low removal efficiencies and complex system setups are not desirable. In this study, we examined a simple costeffective approach for selective brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The undesired ClO 3 – and BrO 3 – are always formed in radical-based oxidation systems, due to the inevitable reactions between radical and halides. , In the PAA/X – system, ClO 3 – and BrO 3 – were not observed along the reaction. Though the reactions of ClO 3 – and BrO 3 – productions can occur (Table S17), sluggish reaction rates or low reactant concentrations make the intermediates and products insignificant . Indeed, the model simulation showed that the ClO 3 – and BrO 3 – concentrations were consistently below 10 –30 M (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The undesired ClO 3 – and BrO 3 – are always formed in radical-based oxidation systems, due to the inevitable reactions between radical and halides. , In the PAA/X – system, ClO 3 – and BrO 3 – were not observed along the reaction. Though the reactions of ClO 3 – and BrO 3 – productions can occur (Table S17), sluggish reaction rates or low reactant concentrations make the intermediates and products insignificant . Indeed, the model simulation showed that the ClO 3 – and BrO 3 – concentrations were consistently below 10 –30 M (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…productions can occur (Table S17), sluggish reaction rates or low reactant concentrations make the intermediates and products insignificant. 51 Indeed, the model simulation showed that the ClO 3 − and BrO 3 − concentrations were consistently below 10 −30 M (data not shown). In addition, the mass balance was also calculated by the model simulation to investigate the formation of toxic halogenate DBPs in the PAA/X − system (Figure 5a).…”
mentioning
confidence: 97%
“…More specifically, the reported studies have focused on developing different strategies and materials for iodine removal, such as nanoparticles, membrane filters (reverse osmosis, nanofiltration, , ion exchange, , and electrodialysis), electrochemical techniques, , absorption techniques (layered double hydroxides, modified activated carbon, , silver impregnated activated carbon, , silver-doped carbon aerogels, ion exchange resins, , soils, and composites), and oxidants …”
Section: Introductionmentioning
confidence: 99%
“…9 More specifically, the reported studies have focused on developing different strategies and materials for iodine removal, such as nanoparticles, 10 membrane filters (reverse osmosis, 11−14 nanofiltration, 11,13−17 ion exchange, 18,19 and electrodialysis 20 ), electrochemical techniques, 21,22 absorption techniques (layered double hydroxides, 23−28 modified activated carbon, 27,29−31 silver impregnated activated carbon, 32,33 silver-doped carbon aerogels, 34−37 ion exchange resins, 38,39 soils, 40−42 and composites 43 ), and oxidants. 44 There are 37 known isotopes of iodine ( 108 I to 144 I), and all isotopes decay except 127 I, which is a stable isotope of iodine that is used in the applications listed below. In chemistry, 127 I is primarily used in oxidation reactions, 45 iodine.…”
Section: Introductionmentioning
confidence: 99%